Reading on paper or reading digitally? Reflections and implications of ePIRLS 2016 in South Africa - Celeste Combrinck; Nangamso Mtsatse (South African Journal of Education, 2019)
South Africa participated in the electronic version of the Progress in International Reading Literacy Study (ePIRLS) in 2016 but faced many challenges during implementation. Accurate databases on information and communication technologies (ICT) capacity of schools were not available for sampling in Gauteng, many schools had old and/or non-functional hardware and half of the schools had not used their computer laboratories in the last 3 years. Consequently, South Africa was excluded from the international report as the study requirements could not be met. In this paper we examine the implications of the problems experienced in the ePIRLS multiple case study, conducted in 9 schools (n = 277) in Gauteng. Multilevel models were built using data from the nationally representative Grade 4 Progress in International Reading Literacy Study (PIRLS) data from 2011 (n = 15,744) and 2016 (n = 12,810). In the 2016 national study, principals and teachers reported fewer computers and libraries being available for learners than were reported in 2011. Computers and paper-based libraries being available were not significant predictors of reading literacy. Instead, the medium of instruction in the Foundation Phase, school location, gender, and socioeconomic composition of the school predicted reading literacy achievement. The ePIRLS results show no significant difference between paper-based and online reading. While issues of poverty, gender inequality, and historical disadvantage persist, Grade 4 learners may lack adequate opportunities to acquire paper and digital reading skills. We conclude that the most disadvantaged learners have increasingly insufficient opportunities and resources available to attain basic reading skills and this will have negative long-term consequences for South Africa’s educational sector and economy.